Influência da adição de nitrato de cálcio e de PhoslockTM no abatimento dos fluxos de nutrientes e metais na interface sedimento-coluna de água em um sistema lacustre eutrofizado - Oliveira, Aline Fernandes de (2012)
This research project evaluated the changes in the fluxes of nutrients and metals at the sediment-water interface as a result of sediment treatment by the additions of PhoslockTM and calcium nitrate solution. The experiments were executed in situ using mesocosms that were assembled in the Ibirité Reservoir (MG). The calcium nitrate addition experiments showed nutrients flux abatement for Porthophosphate, ammoniacal-N and nitrate-N that were ≥ 90% whilst for the metals Fe and Mn the percentages reached 48 and 69%, respectively, as a result of sediment oxidation promoted by the intensification of denitrification rates. For the PhoslockTM addition the percentages of reduction in the fluxes across sediment-water interface was over 90% for P-orthophosphate and ammoniacal-N, 78% for nitrate-N and for the metals, Fe and Mn, 47 and 50%, respectively, as a result of the increased adsorption capacity of sediments due an excess of adsorbent material left on sediment surface.